(untitled) (Quinto Sol, 2017)
This article analyzes a particular institution that arose to combat epidemic outbreaks: the commissions of residents, focusing particularly on the cholera epidemics of 1867, 1868 and 1873, and the yellow fever epidemics of 1871 and 1886. The commissions of residents have been mostly interpreted by historiography as a response of the society due to the Government’s inaction, mainly at a municipal level. This article revisits this statement and argues that epidemics brought about the possibility to create, reform and transform specific areas of the municipal government, mainly those related to health and hygiene. We have called this process institutionalization vector, because a series of measures and organization forms that appeared at first temporarily due to the cholera and yellow fever epidemics, were then institutionalized. We also argue that the unquestionable relevance of the 1871 yellow fever epidemic should not prevent the study of other epidemic outbreaks that were also very significant in the development of the commissions of residents and, most importantly, contributed to the institutional strengthening of municipal governments. From this standpoint, it is possible to show areas of interaction, subordination, independence and conflict among the commissions of residents and the municipal governments and the provincial government of Buenos Aires.